PENGOPTIMUMAN TIGA FORMULASI SATA PADA BANGSA INDONESIA, MELAYU DAN CINA MELALUI PENILAIAN SENSORI - Rita Hayati (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Optimization of Three Sata Formulation on Indonesian, Malayan, and Chinese through Sensory Evaluation Rita Hayati Fakultas Pertanian Unsyiah, Nanggroe Aceh Darussalam ABSTRACT Result of the study showed that optimum region for sata production using boiled tuna fish, katsoubushi and surimi were 36-40%, 39-85% and 0-12%, respectively. Three formulations were selected for validation study. Two formulation were from acceptance region (F1=0.37 of boiled fish, 0.46 katsoubushi, 0.17 surimi, F2 =0.37 of boiled fish, 0.40 katsoubushi, 0.22 surimi), and one formulation from rejection region (F3 =12.5 of boiled fish, 75 katsoubushi, and 12.5 surimi). The validation of the three optimum points using sensory evaluation showed that formulation F1 was most acceptable followed by F2 and F3. There was significant difference (P≤0.05) between F1 and F2 when compared to F3, thus model equation was able to predict the optimum points.